2013
DOI: 10.1017/s0029665113003613
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR677TT genotype and disease risk: is there a modulating role for B-vitamins?

Abstract: Methylenetetrahydrofolate reductase (MTHFR) is a critical folate-metabolising enzyme which requires riboflavin as its co-factor. A common polymorphism (677C→T) in the MTHFR gene results in reduced MTHFR activity in vivo which in turn leads to impaired folate metabolism and elevated homocysteine concentrations. Homozygosity for this polymorphism (TT genotype) is associated with an increased risk of a number of conditions including heart disease and stroke, but there is considerable variability in the extent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 114 publications
1
24
0
2
Order By: Relevance
“…Also, the lack of measurements of vitamins should be mentioned, especially riboflavin, which has been described as an important nutrient that influences disease risk associated with the MTHFR C677T polymorphism. 13 Furthermore, we do not have information about supplement use in the 22-23-year follow-up. Finally, we did not analyze different types of alcoholic beverages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the lack of measurements of vitamins should be mentioned, especially riboflavin, which has been described as an important nutrient that influences disease risk associated with the MTHFR C677T polymorphism. 13 Furthermore, we do not have information about supplement use in the 22-23-year follow-up. Finally, we did not analyze different types of alcoholic beverages.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Hcy concentrations depend on age, sex and lifestyle variables, such as smoking, alcohol intake, physical activity and nutritional status, especially related to folate and vitamin B deficiencies. 2,4,11,12 As recently discussed by Reilly et al, 13 on the basis of a meta-analysis of randomized trials, a reduction in Hcy concentrations by approximately 25% was demonstrated after supplementation with folic acid, the synthetic form of folate. In addition, single-nucleotide polymorphisms (SNPs) that have an impact on Hcy concentrations are described.…”
Section: Introductionmentioning
confidence: 89%
“…1). Methylenetetrahydrofolate reductase (MTHFR), an important enzyme in the methionine cycle [57], is involved in the removal of circulating homocysteine. MTHFR lies within a linkage region on chromosome 1p36 that is associated with the regulation of BMD [58,59].…”
Section: Gwas Related To Osteoporosis and Osteoporotic Fracturesmentioning
confidence: 99%
“…A C677T nonsynonymous and functional polymorphism has been identified in exon 4 of MTHFR that results in an alanine to valine change. The T-allele variant (valine type) has a lower MTHFR activity than the wild type (C-allele or alanine type) and is also associated with moderately elevated homocysteine levels [57]. An elevated homocysteine level has been recognized as a significant risk factor for fractures [60][61][62], independent of age and BMD, because it is caused by abnormal collagen cross-links during bone calcification [63][64][65].…”
Section: Gwas Related To Osteoporosis and Osteoporotic Fracturesmentioning
confidence: 99%
“…Se encuentra en alimentos como las verduras de hoja verde, legumbres, frutos secos y granos enteros como las almendras [2]. El ácido fólico es de particular interés clínico por su relación con la anemia megaloblástica y diversos trastornos neurológicos relacionados con la carencia de la vitamina [3,4], suplencia perinatal y prevención de defectos del tubo neural [5], metabolismo de la homocisteína y su asociación con eventos vasculares cardiacos y cerebrales [6] y su relación con la disminución del riesgo a padecer diversos tipos de cáncer [7].…”
Section: Introductionunclassified